Metode Ijtihad Dan Dinamika Persoalan Di Kalangan Imam Madzhab - Mohammad Yasir Fauzi; Agus Hermanto; Ismail, Habib; Mufid Arsyad (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. There is no corner of space that is not touched by Islamic law, the difference in legal products from the results of ijtihad scholars is a blessing for the people. The problem is; Why do scholars differ on a religious issue? Aim. This study aims to explore the ijtihad method of madhhab scholars used as a tool to analyze all phenomena that occur, so that the roots of these differences are known.Methods. This research is a type of qualitative research in the form of library research, by exploring the arguments and methods used by scholars who then make legal products that are different from one another.Results. The results of this study indicate that differences are mercy, as long as these differences do not cause division, and always bring benefit with logical arguments and can be accepted by common sense, even though there are two types of differences, namely differences in reason (ikhtilaf al-aql), and differences in morals. (ikhtilaf al-akhlak), differences occur due to unequal contextualization, thus requiring different arguments and methods of ijtihad, resulting in unequal products from one another.